2021
DOI: 10.1186/s40249-021-00818-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of using electronic medication monitors on tuberculosis treatment outcomes in China: a longitudinal ecological study

Abstract: Background In China, an indigenously developed electronic medication monitor (EMM) was designed and used in 138 counties from three provinces. Previous studies showed positive results on accuracy, effectiveness, acceptability, and feasibility, but also found some ineffective implementations. In this paper, we assessed the effect of implementation of EMMs on treatment outcomes. Methods The longitudinal ecological method was used at the county level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…This trial did show a reduction in non-adherence, measured by box-opening, in the intervention group compared with the control group, similar to in our previous study, 6 indicating improved quality of treatment with the intervention. Based on adherence data from these two pragmatic trials and programmatic experience of medication event reminder monitors in 138 counties in China, 21 the China national tuberculosis programme has planned to expand the utilisation of the monitors, albeit with real-time functions, nationwide, in their 14th 5-year plan (for 2021–25).…”
Section: Discussionmentioning
confidence: 99%
“…This trial did show a reduction in non-adherence, measured by box-opening, in the intervention group compared with the control group, similar to in our previous study, 6 indicating improved quality of treatment with the intervention. Based on adherence data from these two pragmatic trials and programmatic experience of medication event reminder monitors in 138 counties in China, 21 the China national tuberculosis programme has planned to expand the utilisation of the monitors, albeit with real-time functions, nationwide, in their 14th 5-year plan (for 2021–25).…”
Section: Discussionmentioning
confidence: 99%
“…The thirty-six included studies were published between 2000 and 2021. They consisted of eleven RCTs (14,15,24,(16)(17)(18)(19)(20)(21)(22)(23), four cluster randomised control trials (25)(26)(27)(28), nineteen seventeen cohort studies (29,30,(39)(40)(41)(42)(43)(44)(45)(46)(47)(31)(32)(33)(34)(35)(36)(37)(38), one records reviews (48) and one quasi trial (49). All thirty-six had a control group and provided estimates of effect: Eleven evaluated community health care worker direct observation therapy (CHWDOT) (24,27,31,38) (14,19,25,26,29,33,39), nine evaluated family direct observat...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The results of these studies showed a treatment success ratio ranged from 1.0-4.33 and the 95% CI fell within 0.98-95.4 values all with no statistical significant effect on treatment success. (30,42,45,46) Suggesting that electronic medication monitor is effective on treatment outcomes especially in the countries with lower economies.…”
Section: Electronic Medication Monitor (Emm)mentioning
confidence: 99%
“…WHO recently encouraged using digital health technologies such as short message service (SMS), video-supported treatment (VOT), and medication event monitoring systems (MEMS) to help TB patients complete treatment ( 2 , 9 ). In China, an electronic medication monitor (EMM) without real-time data transmission has been used in 138 counties in three provinces ( 10 ). A cluster-randomized trial proved that the EMM improved medication adherence in TB patients while SMS did not ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…A cluster-randomized trial proved that the EMM improved medication adherence in TB patients while SMS did not ( 11 ). But the effect of the EMM and SMS on TB treatment outcomes remains controversial ( 10 , 12–15 ). Additionally, the EMM cannot provide real-time medication adherence data which may impede timely intervention from healthcare providers.…”
Section: Introductionmentioning
confidence: 99%